Intradural Extramedullary Metastasis from Primary Carcinoma of Breast via Brachial Plexus Perineural Spread: A Case Report and Review of Literature - Dandekar, Anurag Chandrakant; Chaudhari, Mahesh P. (Asian Journal of Neurosurgery, 2022)
Intradural extramedullary metastasis from breast carcinoma is a rare occurrence. Furthermore, patients with primary breast carcinoma presenting with neurological symptoms in the first place are even rarer, which was the case in our patient. A 60-year-old woman presented with left upper limb monoparesis for 2 years and rapidly progressive weakness in the left lower limb for 1 week. The patient was evaluated and investigated to find primary left breast carcinoma with metastasis to multiple sites including C5-T1 intradural extramedullary spread. The patient was treated surgically, and decompression and tissue diagnosis were achieved to form a base for starting adjuvant therapy and safeguarding further neurological deterioration due to cord compression. In advanced metastatic cancer, preservation of neurologic function is the goal of surgical treatment. Thorough evaluation of patients presenting with a neurological deficit is always mandatory. Patient education is equally important for palliative treatment as well as to help reduce the burden of metastatic diseases.
Keywords: intradural metastasis; breast carcinoma; brachial plexus; brachial plexopathy; perineural spread